2005
DOI: 10.1631/jzus.2005.b0022
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of 99mTc-TRODAT-1 SPECT imaging in idiopathic Parkinson’s disease

Abstract: Abstract:Objective: To investigate the role of 99m Tc-TRODAT-1 SPECT in diagnosis and assessing severity of idiopathic Parkinson's disease (PD). Methods: Thirty-eight patients with primary, tentative diagnosis of PD and eighteen age-matched normal controls were studied with 99m Tc-TRODAT-1 SPECT imaging. The regions of interests (ROIs) were drawn manually on cerebellum (CB), occipital cortex (OC) and three transverse plane slice-views of striatums, the semiquantitative BG (background)/[(OC+CB)/2] were then cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“… 5 suggested that the increased levels of extracellular dopamine found in the striatum of patients with DP is due to decreased striatal dopamine transporter (DAT) functioning and not due to increased rates of release. Their hypothesis is supported by evidence of DAT inhibitors such as cocaine and amphetamine derivatives inducing DP, and of evidence of decreased striatal DAT functioning in secondary causes of DP such as PD 6 …”
Section: Reportmentioning
confidence: 91%
See 1 more Smart Citation
“… 5 suggested that the increased levels of extracellular dopamine found in the striatum of patients with DP is due to decreased striatal dopamine transporter (DAT) functioning and not due to increased rates of release. Their hypothesis is supported by evidence of DAT inhibitors such as cocaine and amphetamine derivatives inducing DP, and of evidence of decreased striatal DAT functioning in secondary causes of DP such as PD 6 …”
Section: Reportmentioning
confidence: 91%
“…Their hypothesis is supported by evidence of DAT inhibitors such as cocaine and amphetamine derivatives inducing DP, and of evidence of decreased striatal DAT functioning in secondary causes of DP such as PD. 6 Dopaminergic neurones encode for the 'salience' or importance of environmental stimuli. In conditions such as PD or schizophrenia, in which dopamine is dysregulated, aberrant salience is assigned to normal stimuli, which then leads onto delusion formation.…”
Section: Reportmentioning
confidence: 99%
“…Vários autores relatam que a progressão nos estádios de HYS correlaciona-se com o declínio motor e com a deterioração da qualidade de vida (BHIDAYASIRI;TARSY, 2012;SCHENKMAN et al, 2001). Por sua vez, estudos de neuroimagem frequentemente sugerem que a redução de potenciais de ligação do corpo estriado e nas subregiões significantemente se correlacionam com a gravidade da doença, representada pela HYS e pela gravidade dos sintomas motores estabelecida pela escala UPDRS (ASENBAUM et al, 1997;GENG et al, 2005;HUANG et al, 2004;…”
Section: Correlação Com Parâmetros Clínicosunclassified
“…Besides rapid eye movement sleep behavior disorder, constipation and hyposmia, clinical biomarkers are paid attention by Chinese neurologists. Radiological methods, such as 99m Tc-TRODAT-1 single photon emission computed tomography (SPECT) [63], 18 F-fluorodeoxyglucose positron emission tomography imaging ( 18 F-FDG-PET) [64], functional magnetic resonance imaging [65] and Iodine-123-meta-iodobenzylguanidine ( 131 I-MIBG) [66] have been put into use. The combinations of several biomarkers in PD have been set up, such as the combination of ‘swallow-tail’ sign and putaminal hypointensity [67].…”
Section: Clinical Researchmentioning
confidence: 99%